Advancing Culturally Relevant Pedagogy in a Secondary Methods Course. (3rd April 2018) - Kumar, Tracey
Abstract : Given changes in the U.S. school-age population, it is crucial that colleges of education prepare teacher candidates to work effectively with students from diverse backgrounds. Because diversity constitutes such a small portion of the curriculum in many teacher education programs, it is crucial that teacher educators find creative ways to incorporate diversity into the courses they teach. In this article a teacher educator at a predominantly White institution in the American Southeast describes how she introduces culturally relevant pedagogy and connects it to the content, activities, and assessments included in the remainder of a course.